2017
DOI: 10.1371/journal.pone.0187758
|View full text |Cite
|
Sign up to set email alerts
|

Habitat- and soil-related drivers of the root-associated fungal community of Quercus suber in the Northern Moroccan forest

Abstract: Soil fungi associated with plant roots, notably ectomycorrhizal (EcM) fungi, are central in above- and below-ground interactions in Mediterranean forests. They are a key component in soil nutrient cycling and plant productivity. Yet, major disturbances of Mediterranean forests, particularly in the Southern Mediterranean basin, are observed due to the greater human pressures and climate changes. These disturbances highly impact forest cover, soil properties and consequently the root-associated fungal communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…Ericoid fungi occur frequently on non ericoid plants, such as conifers, as well as other tree species (Chambers, Curlevski, & Cairney, 2008;Dučić, Berthold, Langenfeld-Heyser, Beese, & Polle, 2009;Jankowiak, Bilański, Paluch, & Kołodziej, 2016;Leopold, 2016;Maghnia et al, 2017;Reininger & Schlegel, 2016;, facilitate seedling growth on stressed soils (Yamaji et al, 2016) and enhance the host N supply from recalcitrant organic sources in nutrient-poor environments (Wei, Chen, Zhang, & Pan, 2016;Wurzburger, Higgins, & Hendrick, 2012). We found a higher fraction of endophytes in Pinaceae than Fagaceae roots.…”
Section: The Dominance Of Mycorrhizal Fungi In Rams Of Fagaceae Andmentioning
confidence: 67%
See 1 more Smart Citation
“…Ericoid fungi occur frequently on non ericoid plants, such as conifers, as well as other tree species (Chambers, Curlevski, & Cairney, 2008;Dučić, Berthold, Langenfeld-Heyser, Beese, & Polle, 2009;Jankowiak, Bilański, Paluch, & Kołodziej, 2016;Leopold, 2016;Maghnia et al, 2017;Reininger & Schlegel, 2016;, facilitate seedling growth on stressed soils (Yamaji et al, 2016) and enhance the host N supply from recalcitrant organic sources in nutrient-poor environments (Wei, Chen, Zhang, & Pan, 2016;Wurzburger, Higgins, & Hendrick, 2012). We found a higher fraction of endophytes in Pinaceae than Fagaceae roots.…”
Section: The Dominance Of Mycorrhizal Fungi In Rams Of Fagaceae Andmentioning
confidence: 67%
“…Similarly, the trophic composition of RAMs along a successional gradient of willows and birches was also relatively stable with a strong enrichment of mycorrhizas (>56% read abundance) compared with saprotrophs and endophytes (together 17%); however, ericoid fungal taxa were enriched in later successional stages (Kolaříková et al., ). Ericoid fungi occur frequently on nonericoid plants, such as conifers, as well as other tree species (Chambers, Curlevski, & Cairney, ; Dučić, Berthold, Langenfeld‐Heyser, Beese, & Polle, ; Jankowiak, Bilański, Paluch, & Kołodziej, ; Leopold, ; Maghnia et al., ; Reininger & Schlegel, ; Toju, Sato, et al., ; Toju, Yamamoto, et al., ), facilitate seedling growth on stressed soils (Yamaji et al., ) and enhance the host N supply from recalcitrant organic sources in nutrient‐poor environments (Wei, Chen, Zhang, & Pan, ; Wurzburger, Higgins, & Hendrick, ). We found a higher fraction of endophytes in Pinaceae than Fagaceae roots.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal communities are well known to differ among habitats and to be patchily distributed (e.g. Grau et al ., ; Maghnia et al ., ; Chaudhary et al ., ), but OMFs have received little attention. Bunch et al .…”
Section: Orchid Mycorrhizal Fungus Identity and Orchid Distribution Amentioning
confidence: 99%
“…Fungal communities are well known to differ among habitats and to be patchily distributed (e.g. Grau et al, 2017;Maghnia et al, 2017;Chaudhary et al, 2018), but OMFs have received little attention. Bunch et al (2013) found that Cypripedium acaule associated with different OMFs in locations with different soil chemistry.…”
Section: Reviewmentioning
confidence: 99%
“…The average depth of the described pedons falls within the range reported in the literature (Dettori et al 2001). Soluble ions, particularly sodium, do not disturb the cork oak, though excess calcium most likely does (Maghnia et al 2017). In fact, at each depth, molar ratios Na/Ca were always higher than 1, while Mg/Ca ratio was at maximum 0.6, and Na/K ratio…”
Section: Discussionmentioning
confidence: 89%